2014
DOI: 10.1038/emm.2014.63
|View full text |Cite
|
Sign up to set email alerts
|

miR-98 suppresses melanoma metastasis through a negative feedback loop with its target gene IL-6

Abstract: Dysregulated microRNA (miRNA) expression has a critical role in tumor development and metastasis. However, the mechanism by which miRNAs control melanoma metastasis is unknown. Here, we report reduced miR-98 expression in melanoma tissues with increasing tumor stage as well as metastasis; its expression is also negatively associated with melanoma patient survival. Furthermore, we demonstrate that miR-98 inhibits melanoma cell migration in vitro as well as metastatic tumor size in vivo. We also found that IL-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…Repressed ALK4 and MMP11 expression affect endothelial cell activity and prevent them from proliferation, spreading, and tube formation [ 48 ]. These results are consistent with a study that shows ectopic expression of miR-98 inhibits B16-F1 cell migration as well as in vivo metastasis and tumor angiogenesis by reducing interleukin-6 (IL-6) level [ 49 ].…”
Section: Mir-98supporting
confidence: 79%
See 1 more Smart Citation
“…Repressed ALK4 and MMP11 expression affect endothelial cell activity and prevent them from proliferation, spreading, and tube formation [ 48 ]. These results are consistent with a study that shows ectopic expression of miR-98 inhibits B16-F1 cell migration as well as in vivo metastasis and tumor angiogenesis by reducing interleukin-6 (IL-6) level [ 49 ].…”
Section: Mir-98supporting
confidence: 79%
“…These all lead to an enhanced amount of vascularization occurring. Another increased factor is the amount of CD31, which is another important indicator of tumor angiogenesis [ 49 ]. It has been hypothesized that the CSCs express many pro-angiogenic factors such as VEGF, which lead to the increased amount of angiogenesis in tumor cells.…”
Section: Long Noncoding Rna Malat1mentioning
confidence: 99%
“…In NSCLC, miR-4500 directly targets LIN28B, which has been consistently reported to be associated with let-7 and miR-98. 22,23 TargetScan, miRDB, and TargetMiner revealed that genes other than LIN28B, such as CDC34, PBX3, and FZD3, were predicted as candidate miR-4500 targets. PBX3 is overexpressed in gastric cancer and prostate cancer 24,25 and promotes CRC migration by regulating the MAPK/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that fascin1 KO BMDCs matured by lipopolysaccharide (LPS) showed reduced secretion of inflammatory cytokines including IL-6 and TNFα. Because IL-6 is shown to promote cell motility of a variety of tumor cell lines (32)(33)(34)(35)(36), we examined whether fascin1-mediated increase in IL-6 is involved in chemotactic migration of DCs. We found that IL-6 signaling is required for effective chemotaxis of mature DCs toward CCL19, thereby linking IL-6 mediated inflammation to chemotaxis of mature DCs.…”
Section: Introductionmentioning
confidence: 99%